Respostas
respondido por:
3
a1 = 12
r = 7
===
an = a1 + ( n -1) . r = an
a1 = 12 + ( 1 -1) .7 = 12
a2 = 12 + ( 2 -1) .7 = 19
a3 = 12 + ( 3 -1) .7 = 26
a4 = 12 + ( 4 -1) .7 = 33
a5 = 12 + ( 5 -1) .7 = 40
PA = (12, 19, 26, 33, 40 )
r = 7
===
an = a1 + ( n -1) . r = an
a1 = 12 + ( 1 -1) .7 = 12
a2 = 12 + ( 2 -1) .7 = 19
a3 = 12 + ( 3 -1) .7 = 26
a4 = 12 + ( 4 -1) .7 = 33
a5 = 12 + ( 5 -1) .7 = 40
PA = (12, 19, 26, 33, 40 )
Helvio:
De nada.
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás